PROBLEMS OF THE DEVELOPMENT OF HOSPITALITY ENTERPRISES IN THE 21ST CENTURY (INNOVATIVE ECONOMY, 2023)
Humenyuk A.M., Okhota V.I. PROBLEMS OF THE DEVELOPMENT OF HOSPITALITY ENTERPRISES IN THE 21ST CENTURYPurpose. The aim of the article is to determination of the main problematic aspects of the development of hospitality enterprises in the 21st century by the main spheres of influence.Methodology of research. The theoretical and methodological basis of the research is the fundamental provisions of modern economic theory, the scientific works of leading scientists in the field of hospitality. The following methods were used to achieve the goal: monographic, systematization, description – to identify and characterize approaches to defining the problems of tourism development in the 21st century; abstract and logical – for expressing one's own assumptions and forming conclusions.Findings. The article summarizes the main problematic aspects of the development of hospitality enterprises in the 21st century by the main spheres of influence. It has been determined what these are, in particular: social and economic problems related to the development of society, its values, transformations of economic relations, the impact of economic crises, etc.; the problem of dependence on transport and mobility of tourists; infrastructure problems; problems of technological support (at the level of digitalization of processes and the level of knowledge and skills of personnel regarding the use of information and communication technologies).It has been proven that social and economic problems are related to barriers to sustainable development in terms of three main components, in particular: social norms, a certain structure of values and the distribution of resources. It was established that the problems of suspension of transport, deterioration of transport connections, which countries face during viruses, economic crises, wars, strikes, political crises cause a reduction in the level of mobility of tourists, which, in turn, is a prerequisite for problems of tourist service at the level of hospitality enterprises . It was determined that problems with transport, in particular, aviation, represent a special threat for enterprises in the field of hospitality focused on international tourist flows. It is noted that transport problems are more characteristic of developing countries. It is indicated that if this issue is resolved, most countries will be able to become attractive for the growth of investments and the development of the hospitality sector. It was noted that the solution to the problems of infrastructural provision involves the creation of an infrastructure that includes both objects of the restaurant, hotel, tourist, excursion sectors, as well as objects of information and communication technologies (broadband and mobile Internet), transport infrastructure, medical infrastructure (although b first medical aid services), other additional infrastructure, the functioning of which can act as an additional factor in increasing the interest of tourists, etc. It was determined that in order to solve the problems of technological support, it is necessary to: create attractive financial and credit conditions that will enable the purchase of the latest digital technologies; increasing the level of readiness of personnel to improve digital skills and knowledge.Originality. Approaches to the identification of problems of the development of hospitality enterprises were systematized, which made it possible to substantiate the direction of their influence on the activities of enterprises and the possibilities of solutions.Practical value. Systematized approaches serve as a scientific basis for determining ways to solve the problems of development of hospitality enterprises in developed and developing countries.Key words: the field of hospitality, digitalization, social and economic problems, the problem of dependence on transport and mobility of tourists, infrastructure problems, problems of technological support, personnel skills, information and communication technologies.
Keywords: the field of hospitality; digitalization; social and economic problems; the problem of dependence on transport and mobility of tourists; infrastructure problems; problems of technological support; personnel skills; information and communication technologi